MODELLING AND PREDICTING OF COMMERCIAL PROPERTY ATTENDANCE BASING ON THE ESTIMATION OF ITS ATTRACTION FOR CONSUMERS (by example of shopping malls) - V. S. Spirina; A. O. Alekseyev (Russian Journal of Economics and Law, 2015)
Objective: to research and elaborate an economic-mathematical model of predicting of commercial property attendance by the example of shopping malls, based on the estimation of its attraction for consumers. Methods: the methodological and theoretical basis for the work was composed of the rules and techniques of elaborating the qualimetry and matrix mechanisms of complex estimation, necessary for the estimation and aggregation of factors influencing the choice of a consumers’ group among many alternative property venues. Results: two mechanisms are elaborated for the complex estimation of commercial property, which is necessary to evaluate their attraction for consumers and to predict attendance. By the example of two large shopping malls in Perm (Russia), it is shown that using both mechanisms in the economic-mathematical model of commercial property attendance increases the accuracy of its predictions (compared to the traditional Huff model). The reliability of the results is confirmed by the coincidence of the results of calculation and the actual poll data on the shopping malls attendance. Scientific novelty: a multi-factor model of commercial property attraction for consumers was elaborated by the example of shopping malls, parameters of complex estimation mechanisms are defined, namely, eight parameters influencing the choice of a shopping mall by consumers. The model differs from the traditional Huff model by the number of factors influencing the choice of a shopping mall by consumers, and by the higher accuracy of predicting its attendance. The article was prepared with financial support of Perm National Research Polytechnic University. Practical significance: the economic-mathematical models, able to predict commercial property attendance, can be used for efficient planning of measures to attract consumers to preserve and develop competitive advantages of commercial property.